Vegetation composition, structure and association at site invaded by Calliandra houstoniana in Bung Hatta Grand Forest Park, West Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Solfiyeni, Winata F, Mildawati, Marisa H. 2024. Vegetation composition, structure and association at site invaded by Calliandra houstoniana in Bung Hatta Grand Forest Park, West Sumatra, Indonesia. Biodiversitas 25: 3608-3616. Invasive plants are plants that can aggressively dominate an ecosystem, thereby disrupting the balance of the ecosystem. Kaliandra (Calliandra houstoniana (Mill.) Standl.), an invasive alien plant species, has notably invaded several conservation areas in Indonesia, including Bung Hatta Grand Forest Park, West Sumatra. This study, conducted from October 2023 to February 2024, aimed to analyze the composition, structure and association of vegetation community affected by C. houstoniana and investigate the association between C. houstoniana and other species within the park. Sampling was conducted using the quadrat method by establishing a 20 × 50 meter observation plot, subdivided into ten 10 × 10 meter subplots for tree level; 5 × 5 meter for sapling and 2 × 2 meter for understorey. We identified all plant species within the sub-plots and measured environmental factors including light intensity, temperature and soil pH. Within the sampling plots, there were 11 families, 13 genera and 14 species at tree level with C. houstoniana exhibited the highest Importance Value Index (IVI = 62.96%). At sapling level, there were 9 families and 12 species with the dominance of C. houstoniana (IVI = 168.47%). Understorey was composed by 15 families and 19 species with Clidemia hirta (L.) D.Don as dominant species (IVI = 29.26%). Shannon-Wienner diversity index (H') was moderate where index for tree, sapling and understory was 2.32, 1.69 and 2.7, respectively. Only a few species managed to coexist and withstand the invasion of C. houstoniana. Association tests, including the Chi-Square Test and Jaccard Index, indicated no significant association between C. houstoniana and other species. The results of Principal Component Analysis (PCA) show that environmental factors, especially light intensity and air temperature, greatly influenced the presence of the two dominant species C. houstoniana and Falcataria falcata (L.) Greuter & R.Rankin, while the presence of Pandanus sp. is influenced by soil pH. The study demonstrated that C. houstoniana negatively impacts the diversity of local species, reducing overall diversity levels in Bung Hatta Grand Forest Park.
Keywords: Association, Calliandra houstoniana, composition, structure, trees